Systematic review of open education resources repository: A gateway for scholarly communication in developing countries - Beth Kachota; Kardo J. Mwilongo (Dar es Salaam University Press, 2026)
Development in information technology has universally led to an increase of the importance of the Open Education Resources Repository. This has been of great help in achieving the sustainable development goals on the promotion of quality education and supporting innovation in the community. The technology of open education resources repository has been prominent since 2010 and comprehensively adopted in developed countries. However, it has been dynamically improving in developing regions though its performance fairly convinces appreciations on the invested initiatives. This paper establishes the need to examine the users’ awareness of the repository, performance and influencing factors on the performance of open education resources repositories in developing countries. A systematic review of literature was employed in which 25 research papers were investigated. The papers were searched from four aggregate tools, namely Google Scholar, Research Gate, Open Praxis and Refseek. The Excel computer application software was used to analyse quantitative data whereas qualitative data were subjected to content analysis. Among other things, higher learning institution open education resource repositories in developing countries are becoming common among the academic community. Their performance is significantly remarked in erratic context between regions and diagnostically hampered by varying factors, including technological and infrastructural aspects, financial disputes, environmental and institutional issues. On this, the institutional management support committed to creating open access resources. These resulted to minimal satisfaction on the contribution of the repositories among the scholars. Such open education resources repository guidelines including policy, procedures and standards impacted the repositories performance. The paper encourages on the need for improving information resources acquisition, efforts on raising awareness, dissemination, advocacy, marketing, and management and user support services. However, open education resources repository policy needs to be improvised for quality control and procedures for backup to enhance security, intrusion and mitigation of the effects of potential disasters and fostering sustainability of the open education resources repository